Issue Management in Political Marketing: A Case Study of the North Sumatra Regional Election in 2024 - Azwita, Nuke; Heryanto, Gun Gun (Jurnal Pendidikan Indonesia, 2025)
North Sumatra has become an interesting political battleground, particularly between the Bobby Nasution-Surya and Edy Rahmayadi-Hasan Basri candidate pairs, ahead of the 2024 regional elections.  This paper explores these political dynamics through a qualitative descriptive approach, utilizing in-depth interviews with political observers and potential voters, as well as document analysis to collect primary and secondary data. Thematic analysis was applied to identify patterns in issue management strategies. The research reveals the key issues that influence people's preferences, such as infrastructure development, public services, and health. The findings show an increase in community engagement, especially among the younger generation, who are becoming more critical in their choices. Inclusive and transparent communication strategies are key to building public trust, while social media plays an important role in shaping perceptions of candidates, despite the challenges of disinformation. The conclusion of this study emphasizes the importance of strategy adaptation by candidate pairs to meet public expectations and drive the desired positive change in North Sumatra.